Current status of the treatment of degenerative mitral valve regurgitation - Coutinho, Gonçalo (2021)
Degenerative mitral valve disease (myxomatous degeneration or fibroelastic deficiency) is the most common indication for surgical referral to treat mitral regurgitation. Mitral valve repair is the procedure of choice whenever feasible and when the results are expected to be durable. Posterior leaflet prolapse is the commonest lesion, found in up to two-thirds of patients. It is the easiest to repair, particularly when limited to one segment. In these cases, rates of repairability and procedural success approach 100%, and there is now ample evidence that the immediate and long-term results are better than those of valve replacement. Notably, minimally invasive valvular procedures, surgical or interventional, have attracted increasing interest in the last decade. When performed by experienced groups, mitral valve repair is unrivaled irrespective of the severity of lesions, from simple to complex, which leaflets are involved, and the type of degenerative involvement (myxomatous or fibroelastic). Its results should be viewed as the benchmark for other present and future technologies. By contrast, percutaneous mitral valve repair is still in its infancy and its results so far fall short of those of surgical repair. Nevertheless, continued investment in transcatheter procedures is of great importance to enable development and improved accessibility, particularly for patients who are considered unsuitable for surgery. In this review, we analyze the current status of management of degenerative mitral valve disease, discussing mitral valve anatomy and pathology, indications for intervention, and current surgical and transcatheter mitral valve procedures and results.